Anti-aging Nutrients with Health Beneficial Effects - Katakura, Yoshinori (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Recently, many kinds of foods and food-derived nutrients have been reported to show health-beneficial effects. In particular, some foods and food-derived nutrients have shown anti-aging effects on several organs and tissues, such as brain, muscle, skin, intestine, and so on. In some kinds of foods, the molecular basis of their functionalities (e.g., anti-brain aging, anti-sarcopenia, and anti-skin aging) and inter-tissue networks activated by these foods mediated by exosomes, cytokines, and immune cells have been clarified in detail.